2015
DOI: 10.1097/mcp.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Obesity hypoventilation syndrome

Aaron M. Pierce,
Lee K. Brown

Abstract: OHS is a complex multiorgan system disease process that appears to be driven by adaptive changes in respiratory physiology and compensatory changes in metabolic processes, both of which are ultimately counter-productive. The diurnal hypercapnia and hypoxia induce pathologic effects that further worsen sleep-related breathing, resulting in a slowly progressive worsening of disease. In addition, leptin resistance in obesity and OHS likely contributes to blunting of ventilatory drive and inadequate chemoreceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Hypoxemia is a critical component of respiratory diseases. Before the development of a persistent hypoxemia, a nocturnal desaturation is observed in COPD patients (Kent et al, 2011; Lewis and O’Halloran, 2016) or in patients with obesity hypoventilation syndrome (Pierce and Brown, 2015). Identifying novel therapeutic targets in these patients appear to be still necessary as they are characterized by multiple troubles leading to an increased cardiovascular risk (Kent et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia is a critical component of respiratory diseases. Before the development of a persistent hypoxemia, a nocturnal desaturation is observed in COPD patients (Kent et al, 2011; Lewis and O’Halloran, 2016) or in patients with obesity hypoventilation syndrome (Pierce and Brown, 2015). Identifying novel therapeutic targets in these patients appear to be still necessary as they are characterized by multiple troubles leading to an increased cardiovascular risk (Kent et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Central obesity and increased neck circumference are predisposing factors for OSA [ 95 , 96 ]. The resulting reduction or interruption of airflow, which occurs despite inspiratory effort, causes poor alveolar ventilation and oxyhemoglobin desaturation and, in cases of prolonged events, a progressive increase in the arterial partial pressure of carbon dioxide [ 97 ].…”
Section: Reviewmentioning
confidence: 99%
“…Compared with eucapnic obese patients, patients with OHS have severe upper airway obstruction, restrictive pulmonary damage, decreased central respiratory drive, increased incidence of pulmonary hypertension, and increased mortality [ 100 ]. Among the possible mechanisms involved in the pathogenesis of OHS, some studies have reported damage to respiratory mechanics caused by obesity, leptin resistance leading to central hypoventilation, respiratory sleep disorders, and impaired compensatory responses to acute hypercapnia [ 97 , 100 , 102 ]. With respect to pulmonary function, patients with OHS present a reduction in chest wall compliance of approximately 2.5-fold compared to patients with eucapnic obesity, as well as increased pulmonary resistance that is likely secondary to the reduction in FRC [ 100 ].…”
Section: Reviewmentioning
confidence: 99%
“…Recently, accumulating evidence points to leptin action upstream of disordered breathing. Clinical data from individuals with obesity hypoventilation syndrome suggest that leptin resistance contributes to a reduction in HCVR and HVR likely via an impaired chemosensitivity ( 172 ). Leptin deficient ob/ob mice exhibit a disordered breathing phenotype ( 104 ), including a reduction in HCVR ( 105 ), and treating ob/ob mice with leptin improves ventilation within 3 days, before significant weight loss occurs ( 105 ).…”
Section: Leptinmentioning
confidence: 99%